1986
DOI: 10.1007/bf00715006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weekly training distance on fractional utilization of maximum aerobic capacity in marathon and ultramarathon runners

Abstract: This study was designed to examine the interrelationships between performance in endurance running events from 10 to 90 km, training volume 3-5 weeks prior to competition, and the fractional utilization of maximal aerobic capacity (%VO2max) during each of the events. Thirty male subjects underwent horizontal treadmill testing to determine their VO2max, and steady-state VO2 at specific speeds to allow for calculation of %VO2max sustained during competition. Runners were divided into groups of ten according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
3

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 29 publications
4
70
1
3
Order By: Relevance
“…Peak treadmill running velocity was determined during a maximal test on a horizontal, motor-driven treadmill (Powerjog EG30 Sports Engineering, Birmingham, UK), as previously described by Scrimgeour et al (1986). The treadmill was calibrated before all maximal tests and the subsequently described trials.…”
Section: Peak Treadmill Running Velocitymentioning
confidence: 99%
“…Peak treadmill running velocity was determined during a maximal test on a horizontal, motor-driven treadmill (Powerjog EG30 Sports Engineering, Birmingham, UK), as previously described by Scrimgeour et al (1986). The treadmill was calibrated before all maximal tests and the subsequently described trials.…”
Section: Peak Treadmill Running Velocitymentioning
confidence: 99%
“…In marathon finishers, the longest mileage covered per training session is the best predictor for a successful completion of a marathon (25), and the number of training sessions per week and the number of years training were the best predictors of competitive performance at the marathon distance (22). Scrimgeour et al (26) found that runners training for more than 100 km per week have significantly faster race times over 10 to 90 km than athletes covering less than 100 km. According to Billat et al (27), top class marathon runners train for more total kilometres per week and at a higher velocity than runners at a lower level.…”
Section: Discussionmentioning
confidence: 99%
“…Runners who perform a high volume of endurance training tend to be more economical (Scrimgeour et al, 1986), which has led to the suggestion that running high mileage (>70 miles per week) seems to improve running economy (Scrimgeour et al, 1986;Sjodin & Svedenhag, 1985;Jones & Carter, 2000). However, it is unknown whether the relationship between training volume and economy is cause and effect or that the most economical runners are simply capable of training with a higher volume.…”
Section: Economy Of Ventilationmentioning
confidence: 99%